Sifat Kimia Air Tanah Di Wilayah Kelurahan Cemorokandang Kota Malang - Siswoyo, Hari; Bisri, M.; Sholichin, Moh.; Yuliani, Emma; Asmaranto, Runi; A., Wahyu Nafier (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2013)
One aspect that must be considered in order processing groundwater is the groundwater chemical characteristics. The purpose of this research is to assess and mapping the chemical characteristics of groundwater. To determine the chemical characteristics of this groundwater using the method of Pipers Trilinier Diagram with the help AquaChem package version 3.6 for Windows and to mapping the chemical characteristics of this groundwater with the help package Surfer 8. Based on the analysis results, it can be stated that the chemical characteristics of groundwater at the study site is generally has a carbonate hardness (secondary alkalinity) more than 50%, with cations bicarbonat type and anions no dominant type.Key Words: chemichal characteristic, groundwater, pipers trilinier diagram.